Anxiety-Related Factors During Online Learning During The Covid-19 Pandemic In Students In SMAN 3 Cirebon City - Indah Permata Sari; Ahmad Syaripudin; Ramli Effendi (LPPM ITEKES Mahardika, 2021)
The implementation of the study at home policy made some students feel anxious and depressed. The number of tasks given by the teacher makes many students feel stressed in undergoing online learning. This study aims to determine the factors associated with anxiety during online learning during the COVID-19 pandemic in students at SMAN 3 Cirebon City. The research method used is correlational descriptive with a cross sectional approach. The population in this study were all students at SMAN 3 Cirebon City as many as 1093 students. Using simple random sampling, the total sample was 92 students. The instrument used in the form of a questionnaire sheet and data analysis using the Spearman Rank test, namely the significance value of a = 0.05. The results of the study, most of the students had good personal factors (70.7%), good family factors (82.6%), good social factors (60.9%) and good institutional categories (85.9%). There is a relationship between personal factors (p-value = 0.001), family factors (p-value = 0.026), social factors (p-value = 0.054) institutional factors (p-value = 0.001). In future research, it is expected to be able to prepare better supporting facilities as online learning facilities and infrastructure.